1997
DOI: 10.1103/physrevd.56.3439
|View full text |Cite
|
Sign up to set email alerts
|

Preheating–gravitational-wave correspondence

Abstract: The gravitational wave equations form a parametric resonance system during oscillatory reheating after inflation, when cast in terms of the electric and magnetic parts of the Weyl tensor. This is in direct analogy with preheating. For chaotic inflation with a quadratic potential, this analogy is exact. The resulting amplification of the gravitational wave spectrum begins in the broad-resonance regime for chaotic inflation but quickly moves towards narrow resonance. This increases the amplitude and breaks the s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 45 publications
2
22
0
Order By: Relevance
“…Similar peaks in the gravitational wave spectrum have been seen [24,25] in simulations of undamped preheating. These peaks correspond to the resonant and period doubled frequencies.…”
Section: A Gravitational Wavessupporting
confidence: 59%
“…Similar peaks in the gravitational wave spectrum have been seen [24,25] in simulations of undamped preheating. These peaks correspond to the resonant and period doubled frequencies.…”
Section: A Gravitational Wavessupporting
confidence: 59%
“…2). Subsequently we expect the oscillations in χ 0 to produce a secondary resonance due to the self-interaction and non-linearity of Eq's (17,18).…”
Section: B Non-minimal Preheatingmentioning
confidence: 98%
“…It has been shown using the electric and magnetic parts of the Weyl tensor [18] that there exists a formal analogy between the scalar field and graviton cases during resonant reheating. Here we will show that the correspondence also holds in the Bardeen formalism.…”
Section: The Graviton Casementioning
confidence: 99%
See 1 more Smart Citation
“…Recently Easther and Lim [14] (see also Ref. [15,16,17]) have suggested that large density inhomogeneities on sub-Hubble scales during preheating at the end of inflation could generate a gravitational wave background that might be detectable by future gravitational wave experiments such as Advanced LIGO [18].…”
Section: Introductionmentioning
confidence: 99%